2015
DOI: 10.1177/1078345815587510
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Chronic Health Conditions of Inmates Newly Admitted to Maximum Security Prisons

Abstract: This study estimated the prevalence of chronic medical conditions and risk predictors of 759 newly admitted inmates in two New York State maximum-security prisons. The most prevalent conditions were respiratory (34.1%), cardiovascular (17.4%), and sexually transmitted diseases (STD; 16.1%); least prevalent were HIV (3.6%), cancer (1.7%), and kidney disease (1.7%). Results of the multivariable logistic regression showed that females had higher risk for all conditions except cardiovascular and liver disease; ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 27 publications
1
52
2
2
Order By: Relevance
“…This is higher than the national prevalence of 5.8% [2,22]. Diabetes prevalence among prisoners used to be the same or lower to the national prevalence [32,34,44,46,47]. This increased diabetes could be related to poor feeding conditions and sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is higher than the national prevalence of 5.8% [2,22]. Diabetes prevalence among prisoners used to be the same or lower to the national prevalence [32,34,44,46,47]. This increased diabetes could be related to poor feeding conditions and sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 93%
“…This condition can reveal or disturb the disease [31]. However, several studies in western countries showed similar or reduced diabetes prevalence among prisoners [32][33][34]. This prevalence could be higher among a particular group of prisoners, especially those over 50 years [35].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity risk factors are complex and multifaceted, comprised of behaviors related to physical inactivity and excess caloric intake, as well as the environment where people live and social conditions, such as education and poverty (CDC 2015 ). Along with behavioral, environmental and social factors, studies have found that antipsychotic agents are associated with weight gain and obesity, which is known to increase risk for diabetes, cardiovascular and other chronic diseases (Bai et al 2015 ; Ghanizadeh et al 2013 ; Henderson et al 2015 ; Jafari et al 2012 ; Zuo et al 2015 ). Antipsychotics also have been linked to the expression of genes related to obesity (Fonseka et al 2015 ; Shams & Muller 2014 ; Tek et al 2013 ; Tiwari et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Offenders (also referred to as prisoners or inmates in some jurisdictions and countries) also are at risk for disproportionate rates of obesity (Maruschak et al 2015 ), along with high prevalence of mental health problems that are treated by medications (Glaze & James 2006 ). Studies have found that adult offenders, a vulnerable and priority population for poor health, gain weight and become obese during their incarceration, contributing to their increased risk for related conditions, such as diabetes and cardiovascular diseases (Bai et al 2015 ; Clarke & Waring 2012 ; Herbert et al 2012 ; Wolff et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity policy reform in the jail setting has important implications for addressing health disparities among those who are incarcerated for extended periods of timeespecially as the majority of those individuals serving time in jail already come from underserved minority populations. [6][7][8] Black men have a 1 in 3 and Latino men have a 1 in 6 lifetime risk of incarceration compared with non-Hispanic white men who have a 1 in 23 lifetime risk of incarceration. 9 These minority and underserved populations, who are overrepresented in incarcerated populations, notoriously have poorer health outcomes.…”
mentioning
confidence: 99%